TINJAUAN PENGEMBANGAN LANDASAN PACU BANDAR UDARA KASIGUNCU KABUPATEN POSO - Adu, Amir S; Barnabas, Peter Lee; Setiawan, Arief (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
Means of airport for landing and take off of aircraft is runway. This writing to determine the direction of runway according to aircraft that serviced, geometric requirements of existingrunway conditions in 2011 and the development of phase II stage 2 in 2030 and runway pavement thickness existing conditions in 2011 and the development of phase II stage 2 in 2030. Method that used to determine the direction of the runway using the wind rose and for geometric runway using the ICAO and FAA as well as for runway pavement thickness using the FAA.From the wind analysis result using the wind rose, the direction of the existing runway 03-21 can be used safely. From the calculation result of the geometric condition of existing runway length obtained in 2011 by ICAO runway at for the Fokker F-28 aircraft while the width of the runway by ICAO and FAA at 30,48 m. The condition of the existing runway has a runway length 1.617 m and a width 30 m, so that the runway has been unable to serve the aircraft.For the conditions of the development of phase II stage 2 in 2030 acquired by the FAA runway length at 2.070 m and width 30,48 m while the length of the runway by ICAO at 2.704 m and a width 45,72 m. Conditions runway geometric phase II development stage 2 has a length 2.100 m and a width 45 m, so the runway is capable of servicing Boeing 737-300 aircraft safely compared with FAA planning method. From the calculation result of runway pavement thickness existing conditions in 2011 earned a total pavement thickness is 38 cm with aircraft plan Xian MA-60. Condition of existing runway has a total pavement thickness is 87 cm so that the Xian MA-60 aircraft can be served safely. For the conditions of the development of phase II stage 2 obtained after the equivalent total pavement thickness is 69,5 m for model 1 and 68,8 cm for the model 2 with aircraft plan Boeing 737-300. Conditions runway development phase II stage 2 has a totalpavement thickness after the equivalent is 77,5 cm, so the Boeing 737-300 aircraft can be served safely.Keyword:Â Runway, airport, Kasiguncu, Poso